2019
DOI: 10.1016/j.landurbplan.2019.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Classification of soundscapes of urban public open spaces

Abstract: It is increasingly acknowledged by landscape architects and urban planners that the soundscape contributes significantly to the perception of urban public open spaces. Describing and classifying this impact, however, remains a challenge. This article presents a hierarchical method for classification that distinguishes between backgrounded and foregrounded, disruptive and supportive, and finally calming and stimulating soundscapes. This four-class classification is applied to a growing collection of immersive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 53 publications
3
34
0
2
Order By: Relevance
“…The on-site collection of the data on the acoustic environment consisted of environmental noise measurements, three-dimensional audio recordings and panoramic pictures, intended for laboratory use, as recommended by the ISO/TS 12913-3: 2019 and applied in recent soundscape studies [39,[71][72][73]. The soundscape assessments were made in laboratory conditions.…”
Section: Field Recordings and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The on-site collection of the data on the acoustic environment consisted of environmental noise measurements, three-dimensional audio recordings and panoramic pictures, intended for laboratory use, as recommended by the ISO/TS 12913-3: 2019 and applied in recent soundscape studies [39,[71][72][73]. The soundscape assessments were made in laboratory conditions.…”
Section: Field Recordings and Measurementsmentioning
confidence: 99%
“…The pictures taken at measurement points and presented to participants are shown in Figure 3. Following the method used by Sun et al [72] and having in mind the significance of the foliage visible to participants noted by Watts et al [75], the image area covered by pixels showing foliage was calculated, as shown in Figure 4. All pictures are featuring clearly noticeable foliage.…”
Section: Selection Of Measurement Points and Visual Stimuli Recordedmentioning
confidence: 99%
“…Part 3 of the ISO 12913 series builds on Part 2 and provides guidelines for analyzing data gathered using only those methods [6]. However, the range of possible methodological approaches to soundscape data collection is much broader and it includes, for instance, laboratory experiments [2,7,8], pseudo-randomized experience sampling [9], and even non-participatory studies [10]. The protocol described in this paper was designed having in mind the need for a relatively large soundscape dataset that could be used for design and modeling purposes, thus trying to expand the scope of soundwalks that typically deal with much smaller samples of participants [11].…”
Section: Introductionmentioning
confidence: 99%
“…Not all environmental sounds are noisy or disturbing and should be avoided. Some sounds should be preserved or even accentuated, because a matching soundscape may support the identity and atmosphere (e.g., lively, calming) of the space [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%